BINDING EFFECT OF ARBITRATION CLAUSE TO THIRD PARTIES: PRIVITY OF CONTRACT DOCTRINE Vs. PIERCING THE CORPORATE VEIL - Y Sogar Simamora; Sujayadi Sujayadi; Yuniarti Yuniarti (Universitas Airlangga, 2018)
The arbitration agreement is the legal basis for the arbitration forum to examine and adjudicate the dispute which arose from a private relationship where the parties agree to settle the dispute in arbitration forum. As an agreement, the arbitration agreement still applies the principles of contract, including the principle of privity of contract. In the doctrine of privity of contract, an agreement is only binding and have legal effect only to the parties, the agreement in principle, cannot provide profit or loss to a third party. In the arbitration agreement, only the parties are bound by the arbitration agreement that can become parties to the case investigation. However, in the development of arbitration practice also shows that a third party, not a signatory to the arbitration agreement can be held accountable through an examination of the arbitration case. Such a situation is possible if the third party is resident as a holding company or shareholder of a limited liability company, in which the limited liability company is bound by an arbitration agreement, and the holding company or shareholder proven to perform actions through a subsidiary or a limited liability resulting harm the other party.